Konstruksi Makna Self Acceptance Dalam Album Mono Karya Boygroup BTS Pada Penggemar ARMY Kota Manado - Adjidji, Suci Alawiyah; Tangkudung, Joanne Pingkan M.; Hera, Leviane Jackelin (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Social life in the era of globalization is increasingly becoming complex and sometimes imposes certain standards and and ultimately causes a lack of self-acceptance within a person. Self-acceptance is the ability of someone to make peace with themselves and accept all their strengths and weaknesses. BTS, a boy group from South Korea with global popularity, is spreading awareness about the importance of self-acceptance for their fans ARMY through an album titled